Non-Coding RNAs in Colorectal Cancer: Their Functions and Mechanisms - Jia, Zimo; An, Jiaqi; Liu, Ziyuan; Zhang, Fan (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a common malignancy with high mortality. However, the molecular mechanisms underlying CRC remain unclear. Controversies over the exact functions of non-coding RNAs (ncRNAs) in the progression of CRC have been prevailing for multiple years. Recently, accumulating evidence has demonstrated the regulatory roles of ncRNAs in various human cancers, including CRC. The intracellular signaling pathways by which ncRNAs act on tumor cells have been explored, and in CRC, various studies have identified numerous dysregulated ncRNAs that serve as oncogenes or tumor suppressors in the process of tumorigenesis through diverse mechanisms. In this review, we have summarized the functions and mechanisms of ncRNAs (mainly lncRNAs, miRNAs, and circRNAs) in the tumorigenesis of CRC. We also discuss the potential applications of ncRNAs as diagnostic and prognostic tools, as well as therapeutic targets in CRC. This review details strategies that trigger the recognition of CRC-related ncRNAs, as well as the methodologies and challenges of studying these molecules, and the forthcoming clinical applications of these findings.